MODEL OF SETTING THE AMOUNT OF FUEL CONSUMPTION FOR THE TRACTION OF DIESEL TRAINS AND RAIL BUSES (Transport systems and technologies, 2022)
The article deals with the issues of determining the fuel consumption for traction of diesel multiple unit trains of the fleet of JSC "Ukrzaliznytsya". The criteria for the optimality of mathematical models are formed and the method of fuel consumption for train traction is considered. The inconsistency of the current method with the requirements of adaptability, hardware-software orientation, ease of use was established, and the non-compliance with the ISO 50001 "Energy Management Systems" standard was determined. The physical process of fuel consumption for traction by diesel rolling stock and the method of substitution by the proposed mathematical model under operating conditions are graphically reflected. The main components of fuel consumption and methods for their determination are established. Based on the law of conservation of mechanical energy, a model for determining fuel consumption is proposed and comprehensive information is provided on all components of the model. The results of the calculation of the impact coefficients are given and a list of technical features of the operation park of JSC "Ukrzaliznytsya" is given. On the basis of the real traction arm Okhtyrka-Smorodino, the fuel consumption for traction, idling and the total amount of energy resources consumed by different types of traction units are established. The recalculation of fuel consumption per 1 passenger of the specified service shoulder is graphically reflected, recommendations are given for the efficient use of traction rolling stock, and the need for the use of automated rationing systems is determined.
Keywords: cost rationing, traction calculations, energy resources, mathematical modeling, traction composition..